2021
DOI: 10.9782/jisne-d-19-00039
|View full text |Cite
|
Sign up to set email alerts
|

Special Education in Saudi Arabia: A Descriptive Analysis of 32 Years of Research

Abstract: Saudi Arabia has produced more peer-reviewed research in the past 10 years than ever before (El-Showk, 2016). The country is leading its Arab counterparts in the annual number of both published scientific research and obtained patents. A review of the published research across topics and fields of study, the research designs used, and the populations targeted, is needed in various fields to move related scientific research forward. The current review addresses the Saudi Arabian research related to special educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Related research into student behavior in Saudi Arabia revealed unfortunate results and stressed the need to adopt positive behavioral practices in schools (Almakadma & Ramisetty-Mikler, 2015 ). The results of the current study suggest that school-wide PBS can be applicable to the educational context in Saudi Arabia without major modifications, helping to improve the chance of advancement in the education systems (Alqahtani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 84%
“…Related research into student behavior in Saudi Arabia revealed unfortunate results and stressed the need to adopt positive behavioral practices in schools (Almakadma & Ramisetty-Mikler, 2015 ). The results of the current study suggest that school-wide PBS can be applicable to the educational context in Saudi Arabia without major modifications, helping to improve the chance of advancement in the education systems (Alqahtani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 84%
“…schools all over the country. According to the Saudi Ministry of Education, there are approximately 316 programs for students who are deaf or have hearing impairments in Saudi Arabia's public schools and 171 programs for students who are blind or have visual impairments (Alqahtani, Alshuayl & Ryndak, 2021). …”
mentioning
confidence: 99%